Algebraic Thinking: Conceptions of Elementary School Teachers - Rodrigues Rézio, Ana Sofia (2014)
Students’ algebraic reasoning, at the beginning of their schooling years, includes the development and promotion of functional thinking and the understanding of mathematical properties, which can be stimulated by solving problems. In the latest Portuguese Program for Mathematics Elementary Education, we do not see the topic Algebra in the first year of school although some other topics include objectives of algebraic nature. This fact showed the importance of research about the introduction of concepts and development of algebraic skills by elementary school teachers. We investigated the concept of algebraic thinking and how it has been addressed, by interviewing 50 teachers from Portugal. The results showed that the respondents agree with algebraic experiences in the early years of school; however, the data showed a considerable distance when compared to the concept of “algebraic reasoning” adopted by the current scientific community have of algebraic reasoning. With regard to activities that contribute to its promotion, problem solving was considered to play an important role in the development of algebraic skills as well as its representation and generalization.